Implementasi Model Pembelajaran PBL untuk Meningkatkan Hasil Belajar Matematika pada Siswa Kelas 1 SDN 23 Ampenan - Ningsih, Agustina Komala; Rokhmat, Joni; Triapuri, Ade Hegar (Lembaga Yasin AlSys, 2023)
Mathematics is a branch of science that has an important role in the development of science and technology, both as a tool in the application of other fields of science and in the development of mathematics itself, where in the learning process there are many formulas, numbers and mathematical symbols. Mathematics is taught from elementary school age with the aim of training a person's thinking power, which makes them creative in solving problems, so that it can increase students' interest in learning. Based on the results of observations carried out at SDN 23 Ampenan, it was found that class I mathematics learning outcomes were very low under KKM and students lacked enthusiasm in the learning process. When learning is taking place there are still many students who do not pay attention to the teacher's explanation during learning because the teacher does not use a learning model and only uses a conventional model so that learning is teacher-centred. Thus, 80% of student learning outcomes are below the average or KKM and only 20% of students achieve the KKM score. Therefore, a learning model is needed that involves student activity during the learning process. Therefore, researchers took a problem based learning model to overcome this problem. This research is a type of classroom action research (PTK) because this research was conducted to observe or observe activities that were deliberately created and occurred in a class with an emphasis on perfecting or improving the learning process.